Efektivitas Media Pembelajaran GeoGebra Terhadap Kemampuan Pemahaman Konsep dan Pemecahan Masalah Matematis Siswa Pada Materi Sistem Persamaan Linear Tiga Variabel Di Kelas X SMK Swasta Budi Setia Sunggal T.A 2025/2026 - Nainggolan, Justri; Hutauruk, Agusmanto J.B; Situmorang, Adi Suarman (Universitas PGRI Semarang, 2026)
This study aims to determine the effectiveness of the GeoGebra learning medium on students’ conceptual understanding and mathematical problem-solving skills regarding the topic of systems of linear equations with three variables in the 10th grade at Budi Setia Private Vocational High School. This study employed a quantitative method using a quasi-experimental design in the form of a pretest-posttest-only control group design. The study population consisted of all Grade 10 students at Budi Setia Private Vocational High School, comprising 5 classes. The sample was determined using purposive sampling, resulting in Class X TKR as the experimental class (30 students) and Class X MP as the control class (30 students). The research instrument consisted of an essay test that had been validated for validity and reliability. Pre-test and post-test data were analyzed using normality tests, homogeneity tests, t-tests, N-Gain, and Effect Size. Calculations for the experimental class showed an average score of 77.80 for mathematical concept comprehension, while the control class had an average score of 68.07. Calculations for the experimental class showed an average score of 73.63 for mathematical problem-solving ability, while the control class had an average score of 66.73. Based on the t-test results, a significance value of 0.001 0.05 was obtained, so the null hypothesis was rejected. The GeoGebra learning tool was found to be effective because it was proven to significantly improve student learning outcomes, as evidenced by a comparison of average post-test scores between classes that used the tool and those that did not. In terms of mathematical concept comprehension, students in the experimental class taught using GeoGebra achieved an average score of 77.80, far surpassing the control class, which averaged only 68.07. This advantage was also consistently evident in the mathematical problem-solving ability indicator, where the experimental class recorded an average score of 73.63, while the control class lagged behind at 66.73. The conclusion of this study is that the GeoGebra learning medium is effective in enhancing students’ mathematical conceptual understanding and problem-solving abilities regarding the topic of systems of linear equations with three variables in Grade 10 at Budi Setia Private Vocational High School.